Patanjali : Emergence of a New Star on the Indian FMCG Horizon - Kapoor, Deepa; Chaudhary, Mona (Indian Journal of Marketing, 2017)
In the present day world, life has become more complex and competitive; people are under more stress than before because of lifestyle leading to various diseases at an early age. The vast field of Ayurveda is gaining popularity across the world because of its amazing therapeutic values. Consumers are demanding more herbal and organic products across different categories of personal and home care. Patanjali Ayurveda Ltd. is one of the new entrants in the Ayurvedic and herbal FMCG sector, but has already created waves across the country, giving tough competition to the established multinational corporations. This research highlights the perception of consumers towards Patanjali products. A total of 150 respondents were surveyed to explore various factors influencing consumers’ purchase for Patanjali products, and the overall attitude towards strategies implemented by Patanjali Ayurveda. The study findings showed that product quality, brand image, and trust are the most important factors influencing consumers’ decision making in selecting Patanjali products. Association of the name of Baba Ramdev is also influencing sales of Patanjali. However, results revealed the average satisfaction from Patanjali products.